KELAYAKAN PROBLEM BASED LEARNING DIPADU STEM UNTUK MENINGKATKAN LITERASI DIGITAL PESERTA DIDIK - Julissa Ruri Alyspa; Suyidno Suyidno; Sarah Miriam (Journal of Banua Science Education, 2022)
Problem of the low literacy assessment the problem of the low digital literacy assessment of students underlies the development of learning tools that aim to improve students' digital literacy. The tools developed combined with STEM consist of lesson plans, teaching materials, LKPD, THB, and digital literacy questionnaires. Development model ADDIE used in this study and the trial used one-group pre-test post-test design. The test subjects were 24 students of class X PMIA 1 SMAN 3 Banjarmasin. The results of the study indicate that: (1) the device is valid because the results of the validation of lesson plans, teaching materials, LKPD, THB, and digital literacy questionnaires meet the valid category; (2) The device is practical, because the lesson plans and student responses meet the practical category; and (3) the device is considered effective, due to the increase in digital literacy and student learning outcomes in the high category. Thus, the PBL combined STEM that was developed is feasible to improve students' digital literacy in learning physics.Keywords: development devices, digital literacy, PBL, STEM. ABSTRAKDi era industri 4.0, penguasaan literasi digital mempengaruhi berbagai bidang kehidupan manusia. Namun, literasi digital tersebut belum dilatihkan dengan baik di sekolah. Perangkat yang dikembangkan dipadukan dengan STEM terdiri dari RPP, materi ajar, LKPD, THB, dan angket literasi digital. Model pengembangan ADDIE digunakan pada penelitian ini dan uji coba menggunakan one-group pre-test post-test design. Subjek uji coba adalah 24 peserta didik kelas X PMIA 1 SMAN 3 Banjarmasin. Hasil penelitian menunjukkan bahwa: (1) Perangkat termasuk valid karena hasil validasi RPP, materi ajar, LKPD, THB, dan angket literasi digital memenuhi kategori valid; (2) Perangkat termasuk praktis, karena RPP dan respon peserta didik memenuhi kategori praktis; dan (3) Perangkat termasuk efektif, karena peningkatan literasi digital dan hasil belajar peserta didik dalam kategori tinggi. Dengan demikian, perangkat PBL dipadu STEM yang dikembangkan adalah layak untuk meningkatkan literasi digital peserta didik dalam pembelajaran fisika.Kata kunci: pengembangan perangkat, literasi digital, PBL, STEM.